The enigma of literature: artificial intelligence, critical conscience and innovation - Huamán Villavicencio, Miguel Ángel (2024)
This paper explores literature and art’s role in human evolution, highlighting their permanence and impact through time. From the origins of language to its current digital transformation, human capacity remains a bulwark against the homogenising tendencies driven by artificial intelligence. It is therefore important to warn against the risk of reducing language to a mere vehicle of information, which could threaten freedom and creation, essential for a critical conscience. The tension between technological progress and the preservation of humanist values is addressed through an analysis that evokes thinkers such as Éric Sadin and Karl Marx. In this way, it is a call to resist the imposition of authoritarian control, which simultaneously advocates the vindication of creative plurality, chance, and affectivity, as motors of new forms of existence.